Developing Web applications with microsoft visualbasic. Net and microsoft visual C#.Net(sách photo) - Jeff Webb (Microsoft Coporation, 2003)
Get self-paced, from-the-source exam preparation and self-assessment for the skills measured by MCP Exams 70-305 and 70-315—core requirements for MCAD and MCSD certification. Features an enhanced testing tool and more labs and code examples.